Tradisi Jamuan Laut Persfektif Islam (Studi Nelayan Pantai Kelang, Desa Sei Naga Lawan Kabupaten Serdang Bedagai) - Datmi, Akbar Rosyidi; Nasution, Mhd. Abdul Hakim; Sabana, M. Fauzi; Ningsih, Lidya (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2023)
This study discusses the relationship between tradition and religion carried out by the fishing community of Pantai Kelang, Sei Naga Lawan Village. The question is asked how the tradition of sea banquets has an Islamic perspective. This paper uses the field study method to describe data clearly and in detail on a phenomenon or event. Sources were obtained through observation, documentation and interviews with village heads, sea handlers, fishermen leaders and community leaders. Data were analyzed through the stages of data reduction, data presentation and drawing conclusions. The results show that the tradition of sea banquets carried out by the fishing community of Pantai Kelang, Sei Naga Lawan Village, in practice does not conflict with Islamic sharia rules, but belief in sea ghosts or sea genies is an act of shirk. Because Islam emphasizes that sustenance and safety on the sea and on land are the sole power of Allah. The relationship between tradition and religion has sharia boundaries that must be understood by the community, especially the fishermen of Kelang Beach, Sei Naga Lawan Village.